Application of Nanotechnology Liquid Organic Fertilizer in Sustainable Hydroponic Cultivation for Urban Food Security - Fevria, Resti; Abdul Razak; Heldi; Nurhasan Syah; Eni Kamal; Edwin (Science & Technology Asia, 2023)
The demand for vegetables in urban areas is increasing along with the increase in population. New urban development also reduces the land available for farming, making it difficult for farmers to meet the increasing demand for vegetables in society. Efforts made to meet the need for vegetables in urban areas include hydroponic cultivation which is very efficient in limited areas of land. The current study, conducted November 2022-August 2023, used multidimensional scaling (MDS). The data obtained came from the results of questionnaires and interviews with hydroponics practitioners in Padang City. The research results of the three dimensions tested are economic, social and environmental. In the economic dimension, hydroponic cultivation has an index value of 51.29. In the social dimension it has an index value of 52.37 and in the environmental dimension it has an index value of 53.68. The three dimensions tested have quite sustainable values. The hydroponic mapping results show that there are 22 hydroponic cultivators with a total accumulated production of 10,000 planting holes/month, which are then distributed to large-scale supermarkets in Padang City with various types of hydroponic vegetables.